A Comparison of Traditional and Contemporary Social Houses in Catarmarca (Argentina). Comfort Conditions and Life Cycle Assessment. (July 2022) - Gazquez, Lucio Augusto Molas; Hernández, Francisco Fernández; López, José Manuel Cejudo
Highlights: LCA compares a traditional and contemporary social house in Catamarca (Argentina). LCA is complemented with the thermal comfort evaluation in a retrofit analysis. The operational energy required is much higher than the embodied energy in both houses. The embodied energy of the vernacular house is about 35% of the contemporary one The thermal behavior of the improved contemporary house is equivalent to the vernacular one Abstract: This paper analyses two social houses, the vernacular and the contemporary, in the region of Catamarca (Argentina). The Life Cycle Assessment (LCA) methodology is applied. The embodied, operational energy, and total CO2 emissions are evaluated, with the aim of evaluating the best solution. The thermal model of the contemporary house, in EnergyPlus, is validated comparing with experimental measurements. The results show that the vernacular house uses 35% of the embodied energy of the contemporary house. In the case of operational energy, the ratio is 62.9%. The embodied energy is much lower than the operational energy in both houses. In addition, the thermal comfort of the users is studied. The number of discomfort hours is very similar, about 48% in a year, although slightly better for the vernacular house. Therefore, the installation of a split system to reach the comfort conditions is mandatory. Finally, some improvements for the contemporary house are proposed. Insulation of walls and roof, solar radiation protections, the increase of the thermal mass of the walls and mechanical night ventilation are evaluated. The best combination improves the contemporary house in terms of total primary energy, CO2 emissions and thermal comfort, being equivalent to the vernacular house.